Multiomics: The Growing Impact of Micro/Nanomaterial‐Based Systems in Precision Oncology: Translating "Multiomics" Technologies (Adv. Funct. Mater. 37/2020). (11th September 2020) - Li, Junrong; Wuethrich, Alain; Dey, Shuvashi; Lane, Rebecca E.; Sina, Abu A. I.; Wang, Jing; Wang, Yuling; Puttick, Simon; Koo, Kevin M.; Trau, Matt
Abstract : In article number 1909306, Simon Puttick, Kevin M. Koo, Matt Trau, and co‐workers discuss the use of micro/nanomaterial‐based systems to facilitate "multiomics" cancer signature profiling in clinical settings. This multiomics signature can provide a complete profile of tumor heterogeneity, as akin to assembling a whole jigsaw puzzle from separate pieces.